High-molecular-mass multicatalytic proteinase complexes produced by the nitrogen-fixing actinomycete Frankia strain BR. - Benoist, P (1992)
A major-high-molecular mass proteinase and seven latent minor proteinases were found in cell extracts and in concentrates of culture medium from Frankia sp. strain BR after nondenaturing electrophoresis in mixed gelatin-polyacrylamide gels. All of these complexes showed multicatalytic properties. Their molecular masses and their sedimentation coefficients varied from 1,300 kDa (28S) to 270 kDa (12S). The electroeluted 1,300-kDa proteinase complex dissociated into 11 low-molecular-mass proteinases (40 to 19 kDa) after sodium dodecyl sulfate activation at 30 degrees C and electrophoresis under denaturing conditions. All of these electroeluted proteinases hydrolyzed N-carbobenzoxy-Pro-Ala-Gly-Pro-4-methoxy-beta- naphthylamide, D-Val-Leu-Arg-4-methoxy-beta-naphthylamide, and Boc-Val-Pro-Arg-4-methyl-7-coumarylamide, whereas Suc-Leu-Leu-Val-Tyr-4-methyl-7-coumarylamide was cleaved only by the six lower-molecular-mass proteinases (27.5 to 19 kDa). Examination by electron microscopy of uranyl acetate-stained, electroeluted 1,300- and 650-kDa intracellular and extracellular proteinase complexes showed ring-shaped and cylindrical particles (10 to 11 nm in diameter, 15 to 16 nm long) similar to those of eukaryotic prosomes and proteasomes. Polyclonal antibodies raised against rat skeletal muscle proteasomes cross-reacted with all of the high-molecular-mass proteinase complexes and, after denaturation of the electroeluted 1,300-kDa band, with polypeptides of 35 to 38, 65, and 90 kDa. Electrophoresis of the activated cell extracts under denaturing conditions revealed 11 to 17 gelatinases from 40 to 19 kDa, including the 11 proteinases of the 1,300-kDa proteinase complex. The inhibition pattern of these proteinases is complex. Thiol-reactive compounds and 1-10-phenanthroline strongly inhibited all of the proteinases, but inhibitors against serine-type proteinases were also effective for most of them.